Peran: Ruang Guru Sebagai Aplikasi Berbasis Mobile Dalam Pekembangan Belajar Bahasa Indonesia Pada Siswa MTS - Viona Nurafiani; Hindun Hindun (BADAN PENERBIT STIEPARI PRESS, 2024)
Ruang Guru is an application Ruang Guru is a popular educational application and has many benefits. Ruang Guru provides a positive role in the use of technology. This research uses a qualitative description method which describes students' experiences in developing their learning abilities and students' responses regarding the application. Data were collected by listening and interviews. MTS students are inseparable from gadgets, they need to know the benefits of gadgets that are good for them. The aim of this research is to describe the benefits of the Ruang Guru application in developing students' learning of Indonesian.